Customer relationship management practices: the impact on organizational performance in SMEs of food manufacturing industry - Siti Hajar, Mohamad; Norfaridatul Akmaliah, Othman; Juhaini, Jabar; Izaidin, Abdul Majid (2014)
The successful implementation of customer relationship management (CRM) practices is becoming widely accepted within marketing and sales department in manufacturing industry. Moreover, establishing the customer relationships have always been an important aspect of business. Hence, this study aims to explain the impact of CRM practices to organizational performance through a proposed conceptual model in Malaysian small and medium enterprises (SMEs) food manufacturing industry. A model developed and empirically tested through survey data obtained from 369 organizations. The results indicated that CRM practices have a significant positive effect on organizational performance. Similarly, the results revealed that enhanced key customer focus and relationship marketing leads to better organizational performance. Market turbulence was found to have a negative moderating effect on the relationship between CRM practices and organizational performance. This paper contributes to existing literature by incorporating CRM practices as a construct in the proposed model. The conclusions drawn have implications for CRM practices of key customer focus, relationship marketing and market turbulence in research literature.